Synthesis, characterisation and antimicrobial activities of cobalt(II), copper(II) and zinc(II) mixed-ligand complexes containing 1,10-phenanthroline and 2,2’-bipyridine - A. Mohamadou; D.M. Yufanyi; A.G. Paboudam; N.B. Ndosiri; P.T. Ndifon; M.O. Agwara (Bulletin of the Chemical Society of Ethiopia, 2010)
Three new 1,10-phenanthroline and 2,2’-bipyridine mixed-ligand complexes of [Co(bpy)(phen)2](NO3)2.2H2O, [Cu(bpy)(phen) H2O) 2]Cl2.2H2O, and [Zn(bpy)2(phen)]Cl2.6H2O were synthesized. The complexes were characterized by elemental, IR and visible spectroscopic analyses and the results indicate that both ligands are coordinated to the respective metal ions giving octahedral complexes. Antimicrobial studies showed that there is increased antimicrobial activity of the metal ions on coordination to the ligands. The water soluble complexes showed antimicrobial activities that are higher than those of the metal salts and 2,2’-bipyridine but lower than those of 1,10-phenanthroline. The copper complex [Cu(bpy)(phen)(H2O) 2]Cl2.2H2O shows the highest activity.